METHODOLOGY OF TEACHING INSTRUMENT PERFORMANCE TO VISUALLY IMPAIRED STUDENTS: PROBLEMS AND SOLUTIONS - Nabiyeva Farog’atxon (Zamonaviy ta’lim va tilshunoslik rivoji, 2026)
This article examines the key pedagogical challenges arising in teaching instrument performance to visually impaired and low-vision students, and the practical ways to address them. The article analyzes the activation of auditory and tactile senses as the primary learning channels, learning musical notation through touch (tactile Braille notation system), verbal instruction methodology, and creating an inclusive environment in group learning. The research findings indicate that the musical learning potential of visually impaired students is no lower than that of their sighted peers, however it requires special skills and patience from the educator.